One Hundred Years of General Relativity:From Genesis and Empirical Foundations to Gravitational Waves, Cosmology and Quantum Gravity - Wei-Tou Ni (World Scientific Publishing Co., 2017)
The aim of this two-volume title is to give a comprehensive review of one hundred years of development of general relativity and its scientific influences. This unique title provides a broad introduction and review to the fascinating and profound subject of general relativity, its historical development, its important theoretical consequences, gravitational wave detection and applications to astrophysics and cosmology. The series focuses on five aspects of the theory: Genesis, Solutions and Energy Empirical Foundations Gravitational Waves Cosmology Quantum Gravity The first three topics are covered in Volume 1 and the remaining two are covered in Volume 2. While this is a two-volume title, it is designed so that each volume can be a standalone reference volume for the related topic.